3D porous carbon networks with highly dispersed SiOx by molecular-scale engineering toward stable lithium metal anodes. Issue 43 (7th May 2019) - Lu, Zhitao; Liu, Shaohong; Li, Chuanfa; Huang, Junlong; Wu, Dingcai; Fu, Ruowen
Abstract : Benefiting from a high-porosity interconnected structure and lithiophilic SiO x nanodomains, CNT@SiO x –C shows great advantages as 3D hosts toward stable Li plating/stripping. Abstract : 3D porous carbon networks with highly dispersed SiO x have been successfully prepared by molecular-scale engineering with 1D molecular-brush precursors. Benefiting from the high-porosity interconnected structure and the lithiophilic SiO x nanodomains, the as-obtained composites show great advantages as 3D hosts to achieve stable Li plating/stripping.